A Matter of Time: The Necessity of Temporal Language in Research on Health Conditions that Present with Autism Spectrum Disorder - Rubenstein, Eric (Autism Res, 2018)
Relatively consistent findings from recent studies using population-level data identify heightened physical and psychiatric morbidity in autistic people compared to the general population. Health problems that commonly present with autism spectrum disorder (ASD) are generally discussed in the literature as ‘co-occurring’ or ‘comorbid’ regardless of their known or hypothesized causal mechanisms. In this commentary, we introduce a new temporally-focused terminology to describe health conditions that present with ASD. Emphasizing the temporal development of health conditions in research will help the field to understand whether conditions are: (1) ‘truly co-occurring’ (share an etiologic origin with ASD in utero, are a defining characteristic of a subphenotype), (2) ‘resulting’ (caused by ASD related disparity or the health effect of behaviors developed to cope with ASD symptoms); or (3) ‘associated’ (conditions more common in individuals with ASD with etiology not yet known or hypothesized; or an artifact of diagnostic process or trends). Whether a health condition is ‘truly co-occurring,’ ‘resulting,’ or ‘associated’ has implications for how we design interventions to prevent and treat health conditions in people on the autism spectrum. Ultimately, we think that using clear and temporally-focused language can set us on a path to better deduce etiology and develop effective prevention and intervention efforts for health conditions that impact the lives of autistic individuals. We hope that this approach to temporal language to describe health conditions that present with ASD promotes thought and discussion in the research, advocate, and autistic community.